2020
DOI: 10.1007/jhep04(2020)166
|View full text |Cite
|
Sign up to set email alerts
|

Isolated photon and photon+jet production at NNLO QCD accuracy

Abstract: We discuss different approaches to photon isolation in fixed-order calculations and present a new next-to-next-to-leading order (NNLO) QCD calculation of R γ 13/8 , the ratio of the inclusive isolated photon cross section at 8 TeV and 13 TeV, differential in the photon transverse momentum, which was recently measured by the ATLAS collaboration.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 67 publications
1
75
0
Order By: Relevance
“…The prediction is systematically lower than the data by up to 20% at low E γ T but is closer to the data at higher E γ T , consistent with the results of such comparisons in pp collisions at LHC energies [9,10]. A recent calculation of isolated photon production at NNLO found that the predicted cross-sections were systematically larger at low E γ T than the NLO prediction [46], and thus may provide a better description of the data in this and previous measurements.…”
Section: Resultssupporting
confidence: 83%
“…The prediction is systematically lower than the data by up to 20% at low E γ T but is closer to the data at higher E γ T , consistent with the results of such comparisons in pp collisions at LHC energies [9,10]. A recent calculation of isolated photon production at NNLO found that the predicted cross-sections were systematically larger at low E γ T than the NLO prediction [46], and thus may provide a better description of the data in this and previous measurements.…”
Section: Resultssupporting
confidence: 83%
“…The parameters are chosen to be as loose as possible to minimise a bias from the application of the photon isolation requirement at particle level. Since Frixione's criterion requires the upper limit on the transverse energy isolation to be exactly zero at r = 0, the criterion cannot be strictly looser than any non-zero photon isolation requirement at detector or particle level for all r < R. The photon isolation requirement is applied (see Table 1) using the procedure described in Section 6; the prescription employed is referred to as 'hybrid-cone isolation' [16,62] since it includes the application of the Frixione's criterion at a small value of ∆R (R = 0.1) and the fixed-cone isolation at ∆R = 0.4 used for the fiducial region of the measurement. Dynamic factorisation and renormalisation scales are adopted (E γ T ) as well as a dynamical merging scale withQ cut = 20 GeV [62].…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…Measurements of inclusive prompt-photon production also provide benchmarks to use in investigating novel approaches to parton radiation [12], next-to-leading-order (NLO) QCD corrections with matched parton showers [13], the relevance of threshold logarithms in QCD and electroweak corrections [14] and NNLO QCD corrections [15][16][17]. More specifically, the production of prompt photons, which is less sensitive to hadronisation effects than that of jets, can be used to pursue an alternative QCD description based on the k T factorisation approach combining off-shell amplitudes and transverse-momentum-dependent parton densities [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations